Fatores de virulência da Escherichia coli associados à importância da vacinação nos suínos - Pereira, Daniele Araujo [UNESP]; Vidotto, Marilda Carlos; Nascimento, Karla Alvarenga [UNESP]; Santos, Anne Caroline Ramos dos [UNESP]; Mechler, Marina Lopes; Oliveira, Luís Guilherme de [UNESP] (FapUNIFESP (SciELO), 2016)
Enterotoxigenic Escherichia coli (ETEC) is the major cause of diarrhea in newborn and weaned pigs. Bacteria adhesion to the host cell is considered a specific phenomenon among fimbrial and non-fimbrial adhesins with their respective receptors on enterocytes. Enteric disorders are related with the fimbriae F4 (K88), F5 (K99), F6 (987P), F41, and F18. In addition to ETEC, another category of E. coli, porcine pathogenic E. coli (PEPEC),can cause diarrhea in pigs; it produces the porcine attaching and effacing-associated (Paa) adhesin in, which is capable to cause a typical lesion known as an attaching and effacing (A/E) lesion. Immunization of sows with adhesin is important to stimulate the production of antibodies and their subsequent transfer to piglets through colostrum. The aim of this paper is to illustrate the main impacts of enteric diseases caused by E. coli in swine production and to highlight the importance of continuing research on this bacterium to improve disease prevention through vaccination.
Virulence factors of Escherichia coli in relation to the importance of vaccination in pigs
Keywords: Colibacillosis; Colostrum; Diarrhea; Swine; Vaccines